Mahar dalam Perspektif Maqashid Al-Syari’ah: Analisis Tujuan Syariat dalam Penetapan Hak Perempuan - Winario, Mohd; Sumanto, Dedi; K, Hendri (Journal of Legal Sustainability, 2025)
This study aims to analyze the objectives of the maqāṣid al-syarī‘ah (laws and regulations) in determining the dowry as an instrument for protecting and fulfilling women's rights in Islamic marriage. This study is motivated by the gap between the normative provisions of dowry in Islamic law and social practices, which are often inconsistent with the substantive objectives of Islamic law. This study uses a qualitative approach with library research. Data sources were obtained from the Qur'an, Hadith, and classical and contemporary Islamic jurisprudence and ushul fiqh literature relevant to the concept of dowry and maqāṣid al-syarī‘ah. Data were analyzed using a descriptive-analytical method with a maqāṣid al-syarī‘ah approach, specifically focusing on the aspects of hifẓ al-māl (the need for material goods), hifẓ al-nasl (the need for property), and the principles of justice and benefit. The research results show that dowry from the perspective of maqāṣid al-syarī'ah has the main objective as a form of protection of women's rights, both economically and symbolically. The dowry functions as a guarantee of property ownership for women, an affirmation of men's responsibilities in marriage, and a manifestation of respect for dignity and justice for women. Thus, dowry cannot be understood only as a formal obligation, but rather as a sharia instrument oriented towards the benefit and protection of women's rights in Islamic marriages.